Finding in the Fruška Gora National Park of Cryphia amasina (Draudt, 1931) (Lepidoptera, Noctuidae, Bryophilinae), a species new for the fauna of Serbia - Stojanović D. (Archives of Biological Sciences, 2005)
The present communication reports the finding of Cryphia amasina (Draudt 1931) (Lepidoptera, Noctuidae, Bryophilinae), a species for the fauna of Serbia. Specimens of Cryphia amasina were found in the Fruška Gora National Park, which is located in the North Serbian province Vojvodina. This finding is a result of the more comprehensive entomological research conducted by the author in this area since 2001. different collecting methods (including bulb traps, malaise traps, butterfly nets, and caterpillar breeding) were used in the research. The specimens of Cryphia amasina were caught using a light trap with a 150W bulb in the morning hours.